Analysis of performance of the double rowing shell - Ma, Y.; Zheng, W.; Han, J. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
It is simple and available based on Michell integral method to calculate the wavemaking resistance of rowing at high speed. The rowing is fit for male athletes or female athletes in down wind and down stream condition to use. In long distance training, strength and power should be emphasized. The speed can reach 4.5m/s at least when the athletes have good skill. Athletes should control their weights, and especially, the fat could not be too great